The Impact of Delaying Mie Gacoan’s Halal Certification on Consumer Loyalty - Hakim, Lukmanul; Rosyadi, Imron; Setyawati, Almasah Farah Diah (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2024)
This study aims to evaluate the impact of the delay in Mie Gacoan’s halal certification on consumer loyalty. The delay in halal certification can influence consumer perception and loyalty, yet there is limited research exploring its impact on the food industry in Indonesia. This study employs field research methods, using direct observation and a descriptive qualitative approach to collect and analyze data. The results indicate that most Mie Gacoan consumers know about the delay in halal certification. Despite this, consumers remain highly interested in visiting and purchasing Mie Gacoan products, as they trust that 100% of the raw materials used are safe and have been certified halal. These findings suggest that the delay in halal certification does not significantly affect purchase intentions and consumer loyalty. This research provides new insights into consumer responses to the delay in halal certification, demonstrating that consumer trust in the quality and safety of raw materials can mitigate concerns related to the delay, thus maintaining consumer loyalty to the product.